A Facile 3D Binding Approach for High Si Loading Anodes. (10th September 2016) - Bie, Yitian; Yang, Jun; Lu, Wei; Lei, Zhihong; Nuli, Yanna; Wang, Jiulin
Graphical abstract: Abstract: Silicon is regarded as one of the most promising anode materials for Li-ion batteries owing to its high theoretical capacity (4200 mA h g −1, Li22 Si5 ), but the short cycle life mainly caused by the dramatic volume effect has hindered its practical application. To address this major issue, we report here an effective and scalable approach to fabricate a novel Si electrode via the addition of silane coupling agent, which not only connects silicon and polyacrylic acid (PAA) covalently but also crosslinks PAA, thus forming an entire 3D binding network. The dual functions of 3-amino-propyltriethoxysilane (APTES) in an electrode with 80% Si nanoparticles greatly improves the structural stability during the charge/discharge process, leading to excellent electrochemical performances, such as 1000 mA h g −1 over 1200 cycles and high silicon loading of ca. 4.2 mA h cm −2 . Moreover, this binder system is also effective for the thick silicon/graphite electrodes towards practical application.